Taxonomische Studien zur Hydrophiliden-Gattung Enochrus Thomson, 1859. 6. Teil: Die afrikanischen Arten der Untergattung Lumetus Zaitzev, 1908 und Enochrus s. str. (Coleoptera, Hydrophilidae). - Hebauer, Franz (Contributions to Entomology = Beiträge zur Entomologie, 2004)
The subgenera Lumetus Zaitzev, 1908 and Enochrus s. str. are discussed. A key to all known species of these groups is given and the male genitalia are illustrated.KeywordsInsecta, Coleoptera, Hydrophilidae, Enochrus, systematics, taxonomy, Africa, key, maps.